The Contribution of Work Passion to Sustainable Career Development-Mediating Role of Work Intentions: An Exploratory Study of a Sample of Faculty Lecturers at the University of Mosul - Dina Al-Saji; Thaeir Al-Samman (تنمیة الرافدین)
The study aims to examine the correlation and influence relationships of and influence between work passion and promoting sustainable career development through the mediating role of work intentions. The main problem of the study lies in the following central question: "Does work passion contribute to influencing job intentions, and what are the contributions of both work passion and work intentions to sustainable career development?" Descriptive-analytical has been used in this study. A questionnaire using a five-point Likert scale was the primary data collection tool. The sample of the study consisted of 511 faculty members. The study concluded by accepting all the hypotheses. It reached several conclusions, the most important of which was the discovery of both direct and indirect partial effects of work passion on sustainable career development.  The first is a direct partial effect, and the second is an indirect partial effect through the mediating variable of work intentions. Thus, work intentions partially mediate the relationship between work passion and sustainable career development. The researcher presented a set of recommendations, the most important of which is the necessity for university management to pay attention to each dimension of work passion and work intentions, as this will lead to sustainable career development with its benefits for employees, the university, and the community.